Pemanfaatan AI dalam Pembuatan Media dan Asessment Pembelajaran IPAS - Suhelayanti; Amna Emda; Misbahul Jannah; Wati Oviana; Ridha Ilahi; Rizki Julia Utama (Bansigom Na Publisher, 2024)
The use of artificial intelligence (AI) in media creation and learning assessment of Natural and Social Sciences (IPAS) has a significant impact on the quality of learning. Using AI, innovative and exciting content can be created to improve learning quality. AI can also be used to make IPAS learning more interesting, interactive, and effective, such as the application of Augmented Reality-based technology and automatic online issue correction and real-time feedback. This material was featured in the International Commitment to the Community (PKM) activities carried out by the academic sharing community (KABA) in Takengon Central Aceh, Indonesia. The exposure of this material is expected to help teachers create innovative and exciting learning media by using AI in IPAS learning, especially in media creation and assessment. Using AI in IPAS learning is also expected to make learning more interesting, interactive, and effective as well as strengthen student character education. With dedication to the community, it is expected that the use of AI in learning IPAS can help improve the quality of education at the local and national levels.